The Willingness to forget; Language and history in poul Ricoure - Shbani , Monzer (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
This research Tackles Ricour's perspective of the willingness to forget and the ability of memoey to step ahead the idea if past representation and looking into it as it is one future project. This future which enables humans to recall and forget, forgive and tolerate .all of this is done under what's called by Ricour" the able ego". Afterwards, it reaches a happy memory where by forgetfulness is one image out of many stored in the memory. According to this, the research discusses the beginning of relation ship between history and memory as it is perceived by Ricour, one of interrelation then it discusses the relation of memory and language via its narratives. Narrative, according to Ricour, is means which people use to express their unforgettable past experience, that they need to resurrect the past via narrating and legislating it in stories. Then, it proceeds to handle the idea of willingness to forget and the relation which links forgetfulness to memory, which is one holistic relation, according to Ricour. This means that there is no forgetfulness without recalling and vice versa. Despit that, as perceived by Ricour, memory has always been living in confusion/ hesitation. In other word, you hesitate as to what to recall and what to forget. This has forced or led this research of memory as it is one future project as Ricour assures.it finally concludes with some findings that we sought to have in regards to Ricour's perspective regarding this issus.